2020
DOI: 10.3390/ani10050847
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phytase Supplementation at Increasing Doses from 0 to 1500 FTU/kg on Growth Performance, Nutrient Digestibility, and Bone Status in Grower–Finisher Pigs Fed Phosphorus-Deficient Diets

Abstract: The objective of the current study is to assess the effects of the inclusion of 6-n phytase to a phosphorous-deficient diet on the growth performance (feed intake, average daily gain, and feed conversion ratio), apparent digestibility of calcium and phosphorus, and bone characteristics of grower–finisher pigs. The experimental diets included a phosphorus-deficient diet containing 0 (negative control), 250, 500, 1000, or 1500 FTU/kg of 6-phytase, and a diet formulated to meet the phosphorus nutrient requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
3
7
0
Order By: Relevance
“…This could be an indicator that reducing digestible P and Ca similarly by 0.14, 0.11, and 0.10% points, respectively, in phases 1, 2, and 3 relative to the FEDNA [ 14 ] recommended level in growing–finishing pigs was sufficient to induce negative effects not only on growth performance but also on bone mineralization. In agreement with the data generated with other exogenous phytases [ 42 , 43 ], phytase supplementation at 500 FTU/kg diet in P- and Ca-deficient diets improved the ash, P, and Ca contents in the metacarpal bones of growing pigs. The levels of the metacarpal bones’ dry weight, ash, P, and Ca contents in animals fed with the phytase-supplemented diets became equivalent to those fed with the PC-nutrient adequate diets.…”
Section: Discussionsupporting
confidence: 89%
“…This could be an indicator that reducing digestible P and Ca similarly by 0.14, 0.11, and 0.10% points, respectively, in phases 1, 2, and 3 relative to the FEDNA [ 14 ] recommended level in growing–finishing pigs was sufficient to induce negative effects not only on growth performance but also on bone mineralization. In agreement with the data generated with other exogenous phytases [ 42 , 43 ], phytase supplementation at 500 FTU/kg diet in P- and Ca-deficient diets improved the ash, P, and Ca contents in the metacarpal bones of growing pigs. The levels of the metacarpal bones’ dry weight, ash, P, and Ca contents in animals fed with the phytase-supplemented diets became equivalent to those fed with the PC-nutrient adequate diets.…”
Section: Discussionsupporting
confidence: 89%
“…Wiśniewska et al [ 11 ] and Wu et al [ 28 ] found a positive correlation between percentage improvements in feed efficiency in response to phytase and dietary phytate content, including for diets based on legume seeds, SBM, or RSM [ 29 , 30 ]. Grela et al [ 31 ] observed that a dietary phytase treatment at doses of 500–1000 FTU per kg significantly influenced daily gains and the FCR, but the FI was not affected. Other studies showed that phytase enhanced the utilization of some nutrients, but it was not always connected with increased performance [ 29 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This ability increases with the dose of the enzyme, as reported by other authors [ 10 , 34 ]. Grela et al [ 31 ] found that the administration of 500 FTU of phytase/kg of diet increased bone strength. Kasprowicz-Potocka et al [ 7 ] found that the phytase additive improved the availability of P and Ca in pigs’ diet by 14.34% and 4.08%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…According to nutritional recommendation (NRC, 2012) the ratio of total calcium to digestible phosphorus for growing pigs should amount to 2.1. When they are unbalanced, insoluble and indigestible calcium-phosphorus complexes can form in the intestines (Masuyama et al, 2003, Selle et al, 2009 influencing body mineral balance, achievement of peak bone mass (Heaney et al, 2000), bone mineral density (Sørensen et al, b, 2019Grela et al, 2020), metabolites of bone turnover (Liesegang et al, 2002;Drews et al, 2016;Sørensen et al, 2018 b;Gerlinger et al, 2019), and consequently bone material properties and strength (Huttunen et al, 2007;Grela et al, 2020).…”
mentioning
confidence: 99%
“…However, some authors (Rieger, 2021) indicate that dietary phosphorus has greater, than calcium, impact on bone morphology and mechanic properties. The availability of phosphorus from plant feeds can be increased by the addition of microbial phytase to the animals' diet, which also has a positive effect on the physicochemical status of bones (Grela et al, 2020).…”
mentioning
confidence: 99%